Gospel and spirit issues in New Testament hermeneutics - Fee, Gordon Donald, 1934- (Peabody, MA Hendrickson, 1990)
Includes bibliographical references.
Keywords: Bible -- hermeneutics; Hermeneutics -- Religious aspects -- Christianity; Evangelicalism; Pentecostalism